Implementasi Penggunaan Katalog Untuk Strategi Pemasaran Digital Pengembangan Usaha Masyarakat Di Sektor Lahan Gambut - Deanisa Herawati Putri; Dita Atasa (BADAN PENERBIT STIEPARI PRESS, 2023)
Communities around peat restoration lands are still relatively low in welfare. The presence of the Badan Restorasi Gambut dan Mangrove is a new hope in empowering the businesses of the surrounding community groups. The community groups initially still used traditional marketing techniques and did not have promotional tools to introduce their business products. The limited ability to use digital technology is one of the challenges in digital marketing. Empowerment is carried out by providing assistance, especially in the field of marketing with catalogues. The community group catalogue was prepared through several stages, such as planning, data collection, product branding, product photos, catalogue design and publication. The empowerment activities were held for community business groups around BRGM peat restoration areas such as Riau, Jambi, South Sumatra, Central Kalimantan, West Kalimantan, South Kalimantan, and Papua. The purpose of making catalogues is to encourage community group businesses to be known by the wider community.